PERSEPSI SISWA SEKOLAH DASAR REGULER TENTANG KEBERADAAN SISWA DENGAN KETIDAKMAMPUAN INTELEKTUAL (TUNAGRAHITA) DI SEKOLAH REGULER - , S.N.Purnamawati (Pendidikan Dasar, 2008)
Abstract : Students with intellectual disabilities are often refused to study together in the same class and or schools by regular teachers and students regarding their abilities. However, the human right acts and education for all support opportunities of students with special needs include students with intellectual disabilities to have access into regular schools. The aim of this research is to gain information about perceptions of students to students with intellectual disabilities in regular schools. Located in SDN Gedong 06 Pasar Rebo Jakarta Timur with 60 participants, this study figures that they have an accurate perception toward students with intellectual disabilities who are study at regular schools. It found that the percentage of a whole of accurate perception is 65%.  It seems there is a great information for students with intellectual disabilities who expect to learn in regular schools.